ResQ - Accident Detection and Alerts App - Dr. K. Shailaja; Kandakatla Anusha Reddy (Utilitas Mathematica, 2025)
In today’s world, accidents are major causes of death in many countries. In India, accidents have become more common over the years, where victims often don’t get help in time due to delay in information or miscommunication. To overcome this, we can use smart phones integrated with advanced technology, which plays a major role in our daily lives. In this proposed application it detects the accident using the gyroscope, accelerometer and GPS modules which are inbuilt in smartphone. The Gyroscope is used to detect the sudden changes in orientation or position and movement of the device using a rotating rotor, such as vehicle rollover. These application monitors these readings along with sound data through. A certain limits are set in gyroscope and accelerometer to measure the range, orientation & acceleration of the vehicle which detects the accident and sends the SMS alert to nearby ambulances, hospitals, police station and emergency contacts. It also allows the users to cancel the false alerts that may be triggered by other factors. ResQ bridges the gap between accidents and emergency response, improving rescue efficiency and road safety.